Pengaruh Brand Trust terhadap EWOM Refferal Melalui Purchase Decision (Pada Industri Salon Kecantikan di Kota Medan) - Fadhilah, Annisa Nur; H.M Hermansyur; Handoko, Bagus (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This study aims to determine the effect of brand trust on eWOM referrals through purchasing decisions. The population in this study were 100 respondents from Safa Salon Hair Style and Body Spa in Medan City. The analytical technique used is path analysis. The results showed that brand trust had a positive and significant effect on eWOM referrals mediated by purchasing decisions. The findings of this study demonstrate that brand trust has a direct and beneficial effect on buying decisions. Brand trust has a direct and beneficial effect on EWOM Referrals. EWOM Referral is positively correlatedwith purchase decision. Additionally, brand trust has a substantial favorable effect on EWOM Referrals via purchase decisions On The Beauty Salon Industry In Medan City.